Analysis of Droughts in the Central Region of South Africa and Their Association with SST Anomalies. (25th December 2014) - Edossa, Desalegn C.; Woyessa, Yali E.; Welderufael, Worku A.
Abstract : The objective of this study was to characterise meteorological droughts in the Central Region of South Africa using Standardised Precipitation Evapotranspiration Index (SPEI) and to examine if there is a relationship between drought and El Niño events. The SPEI was used to quantify the precipitation deficit over time and space across the catchment for the time-scales that are important for planning and management of water resources. Based on 12-month time-scale, the total number of drought events identified in the area using SPEI ranged between 13 and 20 during the period of analysis (1952–1999). Considering the effects of event magnitude and duration as severity parameters, the most severe drought event was identified during 1973 followed by 1995 based on 12-month time-scale. Moreover, it was also found that the number of moderate, severe, and extreme drought events identified by SPEI follows increasing trend with decade during the period of analysis. Results of Spearman's rank correlation test revealed that the trends exhibited by mild (SPEI-3 and SPEI-6), moderate (SPEI-12), severe (SPEI-12), and extreme (SPEI-3) drought categories are statistically significant at 5% significance level. The study also revealed that drought events in the central region of South Africa are preceded by El Niño events in the tropical Pacific (Nino 3.4) with an average lag time of 8 months between the onsets of the two events. It was found that hydrological drought events in the study area lag behind meteorological drought events with an average lag time of 7.4 months. Findings of this study can be used to forecast drought events in the area for the proper planning and management of water resources.